THE INFLUENCE OF SPIRITUAL LEADERSHIP STYLE, MOTIVATION AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN EMPLOYEES OF THE REGIONAL INSPECTORATE OF BANTUL DISTRICT - Damayanti, Devi Rosa Fitri; Kirana, Kusuma Chandra; Hadi, Syamsul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Organizational citizenship behavior (OCB) is a positive behavior in organizations that is the main goal of many organizations, OCB can be improved by various factors such as the role of spiritual leadership, always motivating employees and improving organizational culture. The purpose of this study was to analyze the influence of spiritual leadership, motivation, organizational culture and OCB. This study uses a quantitative approach with a saturated sample technique of 46 respondents as primary data, using a questionnaire and processed using SPSS version 26. The findings in this study indicate that spiritual leadership has a positive and significant effect on OCB, but motivation and organizational culture have no significant positive effect on OCB.